KOMUNIKASI INTERPERSONAL PASANGAN SUAMI ISTRI DALAM MENGHADAPI KELAHIRAN ANAK PERTAMA (BABY BLUES SYNDROME) DI KELURAHAN TANJUNG SARI KOTA MEDAN - Sani, Disti Adila; Ritonga, Muhammad Husni (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
The purpose of this study is to ascertain how interpersonal of married couples in facing the birth of their first child (baby blues syndrome) in Tanjung Sari sub-district, Medan City. This study used qualitative methods using methods like interviews with four married couples who live in Tanjung Sari Village to collect data, Medan City, the assurance of witnesses was gotten through snowball testing techniques carried out in multistages. The results of the study show that conflicts arising from changes in interpersonal communication between couples can be overcome by taking a constructive approach (openness, communication and compromise) to help couples maintain the continuity of the relationship during the period of birth of the first child (baby blues syndrome).